The Mexican Ecological Conscience: A Predictive Model - Müller-Pérez, Jessica (2022)
Recently, the number of Mexicans who buy sustainable products has been increasing, which has led to sustainable trade. Therefore, the objective of this study is to determine which variables have a greater effect on Mexicans’ intention to buy green products, their ecological awareness, or moral obligation, and, in turn, to determine the degree to which moral obligation is affected by ecological awareness. A sample of 690 Mexicans was obtained, and a PLS–SEM model was applied for data analysis. The results confirmed that both a moral obligation and ecological awareness explain the intention to purchase green products, with ecological awareness contributing the most to the intention. Furthermore, the findings showed that moral obligation is affected by ecological awareness. The originality of the article is that it contributes to the consumer behavior literature by providing an insight for companies that manufacture sustainable products to understand and promote environmentally conscious consumer behavior. However, there are some limitations that can be addressed in future research.